Bivariate Hahn moments for image reconstruction - Wu, Haiyong; Yan, Senlin (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents a new set of bivariate discrete orthogonal moments which are based on bivariate Hahn polynomials with non-separable basis. The polynomials are scaled to ensure numerical stability. Their computational aspects are discussed in detail. The principle of parameter selection is established by analyzing several plots of polynomials with different kinds of parameters.
Keywords: bivariate Hahn moments; bivariate Hahn polynomials; image reconstruction; pattern recognition